1.
Si:


M = 4 – 15 + 19 – 2
(16 – 23)

N = -19 – 35 – 3 (5 –
7) – ( - 8)

Hallar: M x N1.
Calcular:


A= - 15 + (18 – 16 +
19) – 3 (15 – 4)


B = - 91 – (16 –
17 - 17) – 2 (- 18)
Hallar: A + B

2.
Calcular:


M = -35 – 5 (8 - 16) + (16 – 19) + 26


N = 45 – 35(17 – 23)
– (15 + 16) Hallar: M - N


3. Calcular:


A = - 25 – 17 – 5 (6
– 7) - 3 (- 5)



B = -15 + 19 – 6 (8 –
7) – 2 (-3) Hallar: AxB

1

Respuestas

2014-02-15T13:44:54+01:00
1.   
M = 4 – 15 + 19 – 2(16 – 23)
M= 4 - 15 +19 - 2(-7)
M= 4 - 15 + 19 + 14
M=22

N = -19 – 35 – 3 (5 –7) – ( - 8)
N= -19 - 35 - 3(-2) +8
N=
-19 - 35 + 6 +8
N= -40

Hallar: M x N
= (22)(-40) = -880     
--------------------------------------------------------------------------------------------------------------------------
A= - 15 + (18 – 16 +19) – 3 (15 – 4)
A= -15 + (21) - 3(11)
A=
-15 + 21 - 33
A= -27

B = - 91 – (16 –17  - 17) – 2 (- 18)          
B = -91 - (-18) + 36
B= -91 + 18 + 36
B= -37

Hallar: A + B= (-27) + (-37) = -27 - 37 = -64
----------------------------------------------------------------------------------------------------------------------------
2.    Calcular:
M = -35 – 5 (8  - 16) + (16 – 19) + 26
M= -35 -5(-8) + (-3) +26
M= -35 + 40 -3 + 26
M= 28
 
N = 45 – 35(17 – 23)– (15 + 16)    
N= 45 - 35(-6) - 31
N= 45 + 210 -31
N= 244

Hallar: M -  N= 28 - 244 = -196
----------------------------------------------------------------------------------------------------------------------------
 

3.    Calcular:
A = - 25 – 17 – 5 (6– 7)  - 3 (- 5)
A= -25 -17 -5(-1) + 15
A= -25 -17 + 5 + 15
A= -22

B = -15 + 19 – 6 (8 –7) – 2 (-3) 
B= -15 + 19 - 6(1) + 6
B=
-15 + 19 - 6 + 6
B= 4
Hallar: AxB = (-22)(4)= -88